Study on the Comparison Between Two Models of Frictional Heat Flux in Calculation of Clutch Temperature Field - Cheng Cheng; Li Chen (Jixie chuandong)
Temperature field analysis through finite element model is important in the study of clutch design and control. The frictional heat model is the key to the calculation accuracy of temperature field. Aiming at the two main frictional heat flux models of heat flux uniform distribution and pressure uniform distribution，they are applied to FEM thermal analysis model of clutch respectively to calculate the temperature field varying process with time and space under the extreme condition of continuous sliding. Their results are compared in terms of the maximum temperature, temperature distribution and temperature gradient along the radial direction. In addition, the scope of application of the two models is given.